2010
DOI: 10.1103/physrevb.81.045417
|View full text |Cite
|
Sign up to set email alerts
|

AFM dissipation topography of soliton superstructures in adsorbed overlayers

Abstract: In the atomic force microscope, the nanoscale force topography of even complex surface superstructures is extracted by the changing vibration frequency of a scanning tip. An alternative dissipation topography with similar or even better contrast has been demonstrated recently by mapping the ͑x , y͒-dependent tip damping but the detailed damping mechanism is still unknown. Here we identify two different tip dissipation mechanisms: local mechanical softness and hysteresis. Motivated by recent data, we describe b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Particularly when the FFM tip is subject to stick–slip advancement, this mode becomes especially efficient for resolving structural features. By mapping the power dissipated by these lateral forces, FFM can even detect such elusive structures as moiré patterns on a lattice-mismatched crystal overlayer [ 10 12 ]. One of the most frequent motivations to utilize FFM as a tool in nanotribology is its ability to mimic a single-asperity contact by the junction between a sharp AFM tip and the substrate.…”
Section: Reviewmentioning
confidence: 99%
“…Particularly when the FFM tip is subject to stick–slip advancement, this mode becomes especially efficient for resolving structural features. By mapping the power dissipated by these lateral forces, FFM can even detect such elusive structures as moiré patterns on a lattice-mismatched crystal overlayer [ 10 12 ]. One of the most frequent motivations to utilize FFM as a tool in nanotribology is its ability to mimic a single-asperity contact by the junction between a sharp AFM tip and the substrate.…”
Section: Reviewmentioning
confidence: 99%
“…1a). As an example, using a one-dimensional model consisting of an elastic chain being dragged over a rigid substrate, Negri et al recently showed that friction amplitude modulation could be caused by local mechanical softness and hysteresis at surface defects [27]. This also described friction force variations seen on ultrathin KBr films that had superstructures being deposited on the lattice-mismatched substrates [20].…”
Section: Introductionmentioning
confidence: 96%
“…Noncontact AFM tips oscillating on top of kink-like adsorbate regions (Maier et al, 2008) dissipate significantly more than near in-registry regions. This mechanism is explained by the higher softness and mobility of solitonic regions (Bennewitz et al, 2000;Gauthier and Tsukada, 2000;Hoffmann et al, 2001;Loppacher et al, 2000), and it has been demonstrated by the dynamics of an incommensurate FK chain, forced and probed by a locallyacting oscillation (Negri et al, 2010).…”
Section: F Extensions Of the Frenkel-kontorova Modelmentioning
confidence: 92%